Resurgence of the pertussis: epidemiological analysis of the mesoregion of Campo das Vententes in comparison with the State of Minas Gerais (Research, Society and Development, 2023)
The objective of this study was to investigate the reemergence of pertussis, notification and confirmed cases of the disease in Campos das Vertentes mesoregion, São João del-Rei microregion, state of Minas Gerais, in addition to correlating the number of cases in these regions. Materials and Methods: The incidence in the state of Minas Gerais and in the São João del-Rei town was investigated, through data collection in TABNET, DATASUS, SINAN and bulletins from the Secretary of Municipal Health of São João del-Rei (SMS) -SJDR), from 2008 to 2018, considering the suspected and confirmed cases of the disease. Results: The data allowed informing the community of the surveyed municipalities by providing information that could alert and prevent the reemergence of this disease. Conclusion: Early diagnosis allows successful treatment and reduction of disease complications.